TRANSGRESSION, DESTINY AND FREE WILL: THE PROCESS OF HUMAN FORMATION - Nery Carneiro, Everton (Revista Gênero e Interdisciplinaridade, 2024)
We reflect here on the concepts of destiny, transgression and free will with regard to the process of human formation, dialoguing with Nietzsche, emphasizing that in the face of transgression there is no point in hiding, because the eyes are an opening. With regard to destiny, the promise of modernity is observed that each human being is in their own hands. On free will, Nietzsche claims to be a creation of the ruling strata. We conclude by considering the possibility of understanding destiny as normativity and social order, as the one that predetermines apprehensions and commitments in the family and social area, this opens the way to hyper-moira (transgression) and thus the human being may be accepting or no.